Total phenolic, monomeric anthocyanin content and antioxidant activity of Berberis commutata Eichler fruits - Del Carpio-Jiménez, Carla (Vitae, 2023)
Background: Berberis commutata Eichler is a berry that grows in the Peruvian Andes and has been consumed in the Andes of South America since ancient times. The edible fruits have an intense purple color and are rich in anthocyanins and phenolic compounds that are available from February until May each year. The color of the fruits is a soft purple dye for natural fibers, and many birds use them as food. Objective: This study quantified the total phenolic, monomeric anthocyanin content and antioxidant activity of Berberis commutata Eichler berries. Methods: The total phenolic content was determined by the Folin-Ciocalteu colorimetric assay. Monomeric anthocyanin content was determined by the pH difference method, and the antioxidant activity was measured using the Brand-Williams method. Results: The total phenolic content was 7,490 ± 0.85 mg GAE/100g, and the monomeric anthocyanin content was 70 ± 0.03 mg/100g. The antioxidant activity of the berries showed a tendency to increase with B. commutata extract concentration; an EC50 of 0.91 mg/mL was calculated, indicating a high antioxidant power. Conclusion: Our results showed that B. commutata E. has both high total phenolic content and monomeric anthocyanins comparable to other superfruits and increased antioxidant activity, which means that it is possible to use this berberis species as a functional food.